2015
DOI: 10.1039/c5cp02891d
|View full text |Cite
|
Sign up to set email alerts
|

Intriguing multichannel photoinduced electron transfer in lanthanide(iii)–diphenylamine systems

Abstract: Photoinduced electron transfer (PET) and charge transfer (CT) interactions of trivalent lanthanide ions (Ln(3+)) with a fluorogenic diphenylamine (DPA) donor in aqueous solution have been investigated. Present donor-acceptor systems have a relevance to the leaching out and mitigation of lanthanide ions in the geoenvironment where DPA finds its presence as industrial and agricultural waste. The formation of weak ground state CT complexes in the present systems is confirmed from ground state absorption studies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…The ILs are environmentally benign molten electrolytes, considered as “green solvents”, having unique properties like low vapor pressure, nonflammability, high ionic mobility, and excellent chemical stability. , ILs that possess hydrophobic alkyl chains at their cations show properties similar to conventional surfactants, behaving as surface-active ILs (SAILs). , Being biologically friendly, SAILs have better prospects as cosurfactants than common surfactants to modulate the characteristics of copolymer micelles. , However, only few studies have been reported so far on the use of ILs as cosurfactants, focusing mainly on the changes in the micellar size and aggregation number. To the best of our knowledge, changes in the physicochemical characteristics of micelles, such as micropolarity, microviscosity, solvent relaxation dynamics, and so on, and their consequent effect on bimolecular PET reactions in tetronic–IL mixed micelles have not been attempted so far. Because the necessary structural parameters of T1304–IL mixed micelles using 1-alkyl-3-methylimidazolium tetrafluoroborate ([C n MIm]­[BF 4 ]) series of ILs are readily available in the literature, we have selected these assemblies to study PET reactions involving a series of coumarin dyes as electron acceptors and N , N -dimethylaniline (DMAN) as the electron donor.…”
Section: Introductionmentioning
confidence: 99%
“…The ILs are environmentally benign molten electrolytes, considered as “green solvents”, having unique properties like low vapor pressure, nonflammability, high ionic mobility, and excellent chemical stability. , ILs that possess hydrophobic alkyl chains at their cations show properties similar to conventional surfactants, behaving as surface-active ILs (SAILs). , Being biologically friendly, SAILs have better prospects as cosurfactants than common surfactants to modulate the characteristics of copolymer micelles. , However, only few studies have been reported so far on the use of ILs as cosurfactants, focusing mainly on the changes in the micellar size and aggregation number. To the best of our knowledge, changes in the physicochemical characteristics of micelles, such as micropolarity, microviscosity, solvent relaxation dynamics, and so on, and their consequent effect on bimolecular PET reactions in tetronic–IL mixed micelles have not been attempted so far. Because the necessary structural parameters of T1304–IL mixed micelles using 1-alkyl-3-methylimidazolium tetrafluoroborate ([C n MIm]­[BF 4 ]) series of ILs are readily available in the literature, we have selected these assemblies to study PET reactions involving a series of coumarin dyes as electron acceptors and N , N -dimethylaniline (DMAN) as the electron donor.…”
Section: Introductionmentioning
confidence: 99%
“…27 Bromination in the α-position on 2-methyl-1-azathioxanone has previously been described in the literature using a Wohl-Ziegler bromination. 28,29 However, it was not possible to reproduce this reaction in our labs. Though multiple modifications were attempted in the reaction conditions, the reaction either did not yield the desired molecules in high enough yields to continue the synthetic procedures or gave undesired products.…”
Section: Resultsmentioning
confidence: 98%
“…As an alternative, a patent describing functionalization of the α-position was used with minor modifications, see SI for experimental details. 29,30 In the preferred procedure, see Scheme 1, the parent 2-methyl-1-azathioxanthone derivatives were oxidized using iodide, iron(III)sulfate, TFA, and tert-butyl iodide in DMSO. The reaction was performed at least three times for each derivative, and it was shown that tert-butyl iodide is not required for the oxidation to occur.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonfluorescent chemosensor exhibited an infirm emission spectrum at 355 nm by the excitation at 290 nm, which concomitantly up surged upon consecutive addition of CN – along with the simultaneous red shifting of the peak position (Figure S10; Supporting Information). The bathochromic spectral shift of the sensor in presence of CN – clearly suggested the favorable ICT process. Additionally, the turn-on fluorescence response in presence of CN – may be the consequence of the constraint in the PET as a result of the sensor–CN – interaction. …”
Section: Resultsmentioning
confidence: 99%